Pengaruh Reduksi Kekakuan Elemen Struktur Terhadap Perilaku Struktur Bangunan Gedung Bertingkat Sedang di Kota Padang - Fajri Yusmar; Nevy Sandra; Fitra Rifwan; Eka Juliafad (Jurnal Aplikasi Teknik Sipil, 2023)
The current requirements for structural concrete are SNI 2847 2019 which is an update of SNI 2847 2013. In the latest provisions contained in the table title 6.6.3.1.1 (a) SNI 2847 2019, it is stated that the moment of inertia is allowed to be reduced in elastic analysis at the load level factored. Thus, there is a potential for under design if the stiffness used when determining the magnitude of the earthquake load is reduced stiffness. This study aims to see the effect of using reduced stiffness of structural elements when determining the design seismic load, on the structural behavior of medium-level office buildings in the city of Padang. Structural modeling consists of two models. Model A is a structure with reduced stiffness when determining earthquake loads, while model B is not. The results showed that the fundamental period of the Model B structure experienced a decrease of 17.53% and an increase in base shear of 20.19%. The drift structure of Model B shows a more rigid structure and the maximum internal force has decreased by 9.85%.